Cost‐effectiveness of dapagliflozin as a treatment for heart failure with reduced ejection fraction: a multinational health‐economic analysis of DAPA‐HF. (15th September 2020) - McEwan, Phil; Darlington, Oliver; McMurray, John J.V.; Jhund, Pardeep S.; Docherty, Kieran F.; Böhm, Michael; Petrie, Mark C.; Bergenheim, Klas; Qin, Lei
Abstract: Aim: To estimate the cost‐effectiveness of dapagliflozin added to standard therapy, vs. standard therapy only, in patients with heart failure (HF) with reduced ejection fraction (HFrEF), from the perspective of UK, German, and Spanish payers. Methods and results: A lifetime Markov model was built to estimate outcomes in patients with HFrEF. Health states were defined by Kansas City Cardiomyopathy Questionnaire total symptom score, type 2 diabetes and worsening HF events. The incidence of worsening HF and all‐cause mortality was estimated using negative binomial regression models and parametric survival analysis, respectively. Direct healthcare costs (2019 British pounds/Euro) and patient‐reported outcomes (EQ‐5D) were sourced from the existing literature and the Dapagliflozin And Prevention of Adverse‐outcomes in Heart Failure trial (DAPA‐HF), respectively; the median duration of follow‐up in DAPA‐HF was 18.2 months (range: 0–27.8). Future costs and effects were discounted at 3.0% for the Spanish and German analyses and 3.5% for the UK analysis. In the UK setting, treatment with dapagliflozin was estimated to increase life‐years and quality‐adjusted life‐years (QALYs) from 5.62 to 6.20 (+0.58) and 4.13 to 4.61 (+0.48), respectively, and reduce lifetime hospitalizations for HF (925 and 820 events per 1000 patients for placebo and dapagliflozin, respectively). Similar results were obtained for Germany and Spain. The incremental cost‐effectiveness ratios were £5822, €5379 and €9406/QALY in the UK, Germany and Spain, respectively. In probabilistic sensitivity analyses, more than 90% of simulations were cost‐effective at a willingness‐to‐pay threshold of £20 000/QALY in UK and €20 000/QALY in Germany and Spain. Conclusion: Dapagliflozin is likely to be a cost‐effective treatment for HFrEF in the UK, German and Spanish healthcare systems.